2019
DOI: 10.1523/jneurosci.3229-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Command or Obey? Homologous Neurons Differ in Hierarchical Position for the Generation of Homologous Behaviors

Abstract: In motor systems, higher-order neurons provide commands to lower-level central pattern generators (CPGs) that autonomously produce rhythmic motor patterns. Such hierarchical organization is often thought to be inherent in the anatomical position of the neurons. Here, however, we report that a neuron that is member of a CPG in one species acts as a higher-order neuron in another species. In the nudibranch mollusc, Melibe leonina, swim interneuron 1 (Si1) is in the CPG underlying swimming, firing rhythmic bursts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 57 publications
0
22
1
Order By: Relevance
“…It is currently unclear which ion permeability underlies the sag and the rebound discharge in Si3 neurons. In the previous study, we have shown that the central command neuron, Si1, makes synapses onto Si3 and potentiates the Si3 synaptic strength (Sakurai and Katz 2019). The modulatory effects of Si1 on the membrane excitability of Si3 are of interest and remain to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently unclear which ion permeability underlies the sag and the rebound discharge in Si3 neurons. In the previous study, we have shown that the central command neuron, Si1, makes synapses onto Si3 and potentiates the Si3 synaptic strength (Sakurai and Katz 2019). The modulatory effects of Si1 on the membrane excitability of Si3 are of interest and remain to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, evidence suggests that the output of a neural circuit is remarkably evolutionarily stable. For example, in some of the simplest central pattern generator (CPG) circuits, such as the crustacean pyloric rhythm circuits and the gastropod swimming circuits, the output pattern is relatively consistent between individuals and between species, despite the observed variation in the circuit parameters, for example, synapse strength, wiring pattern, and cellular composition (Goaillard et al, 2009; Prinz et al, 2004; Sakurai & Katz, 2015, 2019; Sakurai et al, 2011). Nevertheless, comparisons between gastropod species showed that changes in the circuit parameters could at times produce changes in homologous CPG circuits (Newcomb et al, 2012; Sakurai & Katz, 2017), suggesting that the output of the circuit is not inherently immutable but is stabilized by compensatory changes in different components of the circuits.…”
Section: Evolution and Development Of Behavioral Neural Circuits In mentioning
confidence: 99%
“…Researchers in the field have been able to employ the aforementioned modern technologies to define motor actions as a function of their natural stereotyped elements, known as behavioral 'modules', 'motifs', 'syllables', or 'primitives'(1, [6][7][8][9][10], where these basic building blocks of motor behavior operate under organizational and hierarchical rules that bear similarities to phonological and syntactical rules that govern language. Modern systems neuroscience approaches have greatly facilitated the investigation of vertebrate motor modules (11)(12)(13), which in invertebrates are even more likely to be interrogated with high sensitivity and precision, largely due to the latter's smaller nervous systems (14)(15)(16). In addition, the next generation of neuroscience discovery capitalizes on developing and studying new non-traditional model species to reveal not only common principles, but also differences in behavioral organization across the tree of life as well as within important clades (17,18).…”
Section: Introductionmentioning
confidence: 99%